2020
DOI: 10.1029/2019wr026788
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Compound Flooding From Landfalling Tropical Cyclones on the North Carolina Coast

Abstract: Tropical cyclone (TC) events are major drivers of compound flooding due to the interaction of wind-driven storm surge and TC rainfall. Traditionally, coastal flood risk models have only taken into account surge flooding, even though it is known that the role of rainfall-runoff is critical. There is limited understanding about the types of TC events that are capable of producing significant compounding and how site conditions at the coast affect the extent to which storm surge and rainfall-runoff interact. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(78 citation statements)
references
References 104 publications
3
75
0
Order By: Relevance
“…• It has the desirable property of detecting the same return periods' intermodel spread in, e.g., four situations where the six CMIP5 models project T fut = (1, 2, 3, 4, 5, 6) ⋅ T pres ; T fut = (1, 1/2, 1/3, 1/4, 1/5, 1/6) ⋅ T pres ; T fut = (1/3, 1/2, 1, 2, 3, 4) T pres ; and T fut = (11,12,13,14,15,16) T pres . (This occurs because ΔT Symmetric (%) increases linearly with a, where T fut = a ⋅ T pres , and decreases linearly with b, where T fut = 1/b ⋅ T pres .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…• It has the desirable property of detecting the same return periods' intermodel spread in, e.g., four situations where the six CMIP5 models project T fut = (1, 2, 3, 4, 5, 6) ⋅ T pres ; T fut = (1, 1/2, 1/3, 1/4, 1/5, 1/6) ⋅ T pres ; T fut = (1/3, 1/2, 1, 2, 3, 4) T pres ; and T fut = (11,12,13,14,15,16) T pres . (This occurs because ΔT Symmetric (%) increases linearly with a, where T fut = a ⋅ T pres , and decreases linearly with b, where T fut = 1/b ⋅ T pres .…”
Section: Methodsmentioning
confidence: 99%
“…The concurrence or short succession of these two hazards can cause compound flooding that can result in larger impacts than would be caused by the individual hazards acting alone [8][9][10][11] , as exemplified by recent events in the Shoalhaven estuary (Australia, 2016) 12 , Ravenna (Italy, 2015) 13 , Cork (Ireland, 2009), and Lymington (United Kingdom, 1999) 14 . Compound flooding occurs when flooding from inland rainfall is enhanced by high meteorological tides that obstruct the gravity-driven drainage of excess fluvial and/or pluvial water into the sea 13,15,16 , or when flooding from meteorological tides is amplified by precipitation 8 .…”
mentioning
confidence: 99%
“…For example, Wahl et al (2015) evaluated the compound impacts of storm surge and precipitation on urban flooding. Gori et al (2020) examined the role of tropical cyclones as agents of compound flooding. Zscheischler et al (2018) found that the interplay and feedbacks between flood, wildfire, heat wave, and drought hazards could exacerbate their collective impacts.…”
Section: Introductionmentioning
confidence: 99%
“…The primary threat of compound flooding in this area results from the interaction of intense eyewall precipitation and storm tides near the coast. However, previous work has shown that outer TC rain bands falling several hours before landfall can result in high river flows in the midstream portion of the river, which can interact with upward propagating storm tides (Gori et al, 2020). High‐resolution modeling is conducted for the portion of the catchment extending from the mouth of the river to 40 km upstream (Figure 1b), while river flows from a larger portion of the basin are captured using an empirical river model (Figure 1a).…”
Section: Methodsmentioning
confidence: 99%